1‐Amino‐5‐methyltetrazole in Energetic 3 d Transition Metal Complexes – Ligand Design for Future Primary Explosives. Issue 2 (3rd February 2021) - Wurzenberger, Maximilian H. H.; Gruhne, Michael S.; Lommel, Marcus; Stierstorfer, Jörg
Abstract: New lead‐free primary explosives are needed for safe future ignition and initiation applications. Especially, ignition by low‐energy laser irradiation has been demonstrated to be a valuable method. For this technology, primary explosives with safer sensitivities are needed. In order to adjust the desired properties of the neat primary explosives, we follow the concept of "energetic coordination compounds" (ECC) in which the ligand significantly alters the final properties. As the result of a study where 1‐amino‐5 H ‐tetrazole (1‐AT) was used as one of the most endothermic ligands, yielding materials with outstanding performance but very high sensitivities, in this work its 5‐methyl analogue 1‐amino‐5‐methyltetrazole (1‐AMT, 1 ) was synthesized and applied as ligand. For a short evaluation, metal perchlorate complexes [M(1‐AMT)6 ](ClO4 )2 of manganese(II), iron(II), and zinc(II) as well as [Cu(1‐AMT)4 (H2 O)](ClO4 )2 were prepared. All compounds were intensively characterized e. g., by XRD, IR, EA, TGA, DTA as well as sensitivity measurements (impact, friction, BDIS, and ESD). The obtained materials show reduced performance but they are safer to handle than the corresponding 1‐AT derivatives. Moreover, the satisfactory performances of ECC 3 and 4 were impressively demonstrated by PETN initiation and laser ignition experiments. Abstract :